CGIAR Excellence in Agronomy Initiative - CGIAR Excellence in Agronomy Initiative (International Institute of Tropical Agriculture, 2024)
The CGIAR Excellence in Agronomy Initiative was launched in 2020 to improve outcomes for smallholder farmers amidst climate change. EiA is supported by the CGIAR Big Data Platform and will combine big data analytics, new sensing technologies, geospatial decision tools, and farming systems research to come up with scalable agronomic innovations for agricultural development. The initiative is not only responding to demand from the public and private sectors but will also help increase efficiencies through stronger collaboration and cross-learning among CGIAR centers and within the broader agronomy R&D ecosystem.